The Relationship between the Intensity of Vocational Program Implementation and the Work Readiness of State Islamic Senior High School Students - Dika Putri Rahayu; Septiand, Erlynd Dwi; Ahmed, Saoud (Jurnal Ilmiah WUNY, 2026)
Background: Vocational programs in Madrasah Aliyah are a strategic approach to bridge the gap between graduate competencies and labor market demands. Objectives: This study aims to analyze the relationship between the intensity of vocational program implementation and the work readiness of MAN students. Method: A quantitative correlational design was employed at MAN 1 Kediri City during the even semester of 2024/2025. A sample of 91 students from a population of 905 was selected through proportionate stratified random sampling. Data were collected using a validated four-level Likert scale questionnaire and analyzed using descriptive and inferential statistics. Result: Pearson Product-Moment correlation analysis revealed r = 0.567 with p < 0.05, indicating a positive and significant relationship with a strong level of closeness between vocational program intensity and student work readiness. Conclusion: The more intense the vocational program implementation, the higher the students' work readiness in terms of technical skills, communication, cooperation, responsibility, and professional attitude. These findings can serve as a basis for strengthening vocational education policy in madrasahs.